Analysis of the implementation of the minimum wage policy in Batu city - Riyanto, Wahyu Hidayat; Firmansyah, Muhammad; Arifin, Zainal (Universitas Ahmad Dahlan, 2025)
A minimum wage policy is essential to maintaining economic stability and encouraging growth. A well-implemented minimum wage can increase employment opportunities and support industrial growth. Therefore, policymakers must consider local economic conditions and industry characteristics when setting minimum wage levels. This study analyzes the implementation process of minimum wage policy in Batu city. In addition, this study also identifies the impact of the policy on worker welfare and economic dynamics and evaluates the challenges and opportunities in implementing the minimum wage policy. This study is qualitative. Data analysis in this study uses a flow model validated through triangulation techniques to ensure accuracy and reliability. The results of this study indicate that 46% of employers comply with the minimum wage policy in Batu City. Workers who receive wages according to the minimum wage positively impact worker welfare; for the MSME category, entrepreneurs in the production and tourism sectors feel that minimum wage changes every year do not affect their ability to pay workers. Therefore, the Batu City government must actively disseminate the minimum wage policy with more optimal supervision.